2003
DOI: 10.1111/j.1469-7793.2003.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal cell communication within local networks in layer 2/3 of rat neocortex

Abstract: Communication relies on the use of a common system of signs or behaviours. Within the neocortex this occurs through the exchange of information locally and interareally using neuronal code in the form of spike trains. Pyramidal cell communication in layer 2/3 represents the response of these cells to afferent and local network signals. The role of local pyramidal cells in the shaping of pyramidal cell firing is determined by their functional connectivity. This process presumably underlies information processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
69
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 48 publications
6
69
0
1
Order By: Relevance
“…5). Connections between bidirectionally connected pairs generated larger EPSPs than unidirectionally connected pairs, consistent with previous reports 3,4,17 , and the RF maps of bidirectionally connected neurons were significantly more correlated than RFs of unidirectionally connected or unconnected pairs (Extended Data Fig. 5).…”
supporting
confidence: 91%
See 3 more Smart Citations
“…5). Connections between bidirectionally connected pairs generated larger EPSPs than unidirectionally connected pairs, consistent with previous reports 3,4,17 , and the RF maps of bidirectionally connected neurons were significantly more correlated than RFs of unidirectionally connected or unconnected pairs (Extended Data Fig. 5).…”
supporting
confidence: 91%
“…A total of 203 pyramidal cells (across 17 mice) recorded in the slice were identified in the in vivo image stacks, and the overall connection rate was 75/520 (0.14). Consistent with previous reports [1][2][3][4][5][6][7][8][9] , the distribution of excitatory postsynaptic potential (EPSP) amplitudes was highly skewed (median EPSP amplitude: 0.19 mV; mean EPSP amplitude ± s.d. : 0.45 ± 0.68 mV; Fig.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Specifically, Holmgren et al (2003) Izhikevich & Edelman (2008). The entries with asterisks are taken from Lefort et al (2009 reported a decrease from 9% probability of two cells within ± 25 µm of each other being connected, to 1% at distances > 100 µm for p II/III -p II/III synapses in visual and somatosensory cortex.…”
Section: Connection Probabilities and Delaysmentioning
confidence: 99%